1994
DOI: 10.1002/polb.1994.090321103
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of interaction energies by the critical molecular weight method: 1. Blends with polycarbonates

Abstract: SYNOPSISThe interaction energies between PS, Pa-MS, and PMMA with several bisphenol-A-based polycarbonates were quantitatively determined from oligomer/oligomer, oligomer/ homopolymer, and homopolymer/copolymer blends. Interaction energies were calculated from the Flory-Huggins theory and the Sanchez-Lacombe equation of state theory using experimental cloud points or miscibility boundaries. Alkyl addition to the phenyl rings of polycarbonate is favorable for miscibility with polystyrene whereas halogenation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 67 publications
1
49
0
Order By: Relevance
“…The blend for commercial molecular weights of both components is immiscible at equilibrium due to an LCST-type phase boundary that lies below the glass transition temperature of the blend. 35 Callaghan et al 37 prepared various PC/PMMA blends by changing molecular weights of both components and then examined their glass transition temperatures and phase behavior. Miscible blends were found for the blend of PC and PMMA at which the molecular weight of either component was lower than certain value.…”
Section: Thermal Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…The blend for commercial molecular weights of both components is immiscible at equilibrium due to an LCST-type phase boundary that lies below the glass transition temperature of the blend. 35 Callaghan et al 37 prepared various PC/PMMA blends by changing molecular weights of both components and then examined their glass transition temperatures and phase behavior. Miscible blends were found for the blend of PC and PMMA at which the molecular weight of either component was lower than certain value.…”
Section: Thermal Behaviormentioning
confidence: 99%
“…[31][32][33][34][35][36][37] It has been concluded that the blend is either miscible or immiscible, depending upon the molecular weights of components that were blended. The blend for commercial molecular weights of both components is immiscible at equilibrium due to an LCST-type phase boundary that lies below the glass transition temperature of the blend.…”
Section: Thermal Behaviormentioning
confidence: 99%
See 3 more Smart Citations